2007
DOI: 10.1364/ao.46.002600
|View full text |Cite
|
Sign up to set email alerts
|

Design of a bright polarized head-mounted projection display

Abstract: In optical see-through head-mounted displays, it has been a common challenge that the displayed image lacks brightness and contrast compared with the direct view of a real-world scene. Consequently, such displays are usually used in dimmed lighting conditions, which limits the feasibility of applying such information displays outdoors or in scenarios where well-lit environments, such as in operation rooms, are required. The lack of image brightness is aggravated in the design of a see-through head-mounted proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In addition, the binocular display allows 3D viewing in case of stereoscopic image capture. Unfortunately, HMDs have, in the past, been large and heavy, 6,7 limited by the size of the display monitors. In recent years, spectacular advances have been made in colordisplay technology, and this miniaturization has been applied ubiquitously, from camera and digital recorder viewfinders to portable video players, game consoles, and cellular phones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the binocular display allows 3D viewing in case of stereoscopic image capture. Unfortunately, HMDs have, in the past, been large and heavy, 6,7 limited by the size of the display monitors. In recent years, spectacular advances have been made in colordisplay technology, and this miniaturization has been applied ubiquitously, from camera and digital recorder viewfinders to portable video players, game consoles, and cellular phones.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Ideally, they should be bright enough to display the endoscopic image in lighted surroundings. 6 They should also be lightweight, allow sufficient peripheral vision, and offer an image quality comparable, or superior to, current liquid-crystal and plasma-monitor technology.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated designs to the optical system [35][36][37].The parameters used to describe an NED are the same no matter what optical design approach is used. In order to design a NED with high imaging performance and high vision comfort, these parameters should be well considered and optimized: field of view (FOV) , eye relief, exit pupil [35], interpupillary distances (IPD) and apparent distance.…”
Section: Optical Systemmentioning
confidence: 99%
“…To address this problem, a polarized HMPD (p-HMPD) was proposed [15], and a prototype based on a pair of transmissive AMLCDs was recently designed [16]. By carefully manipulation of the polarization states of the light propagating through the system, a p-HMPD can potentially be three times brighter than a traditional nonpolarized HMPD design using the same microdisplay technologies.…”
Section: Introductionmentioning
confidence: 99%